RNA metabolism in trypanosomes - Bindereif, Albrecht (Nucleic Acids and Molecular Biology, 2012)
Trypanosomes are unicellular protozoa of ancient evolutionary origin that are responsible for several tropical diseases, such as African sleeping sickness. Over the last few decades, research in trypanosome biology has revealed many unique and fascinating features, many of which have helped to establish new paradigms in other biological systems. This applies in particular to studies in gene expression and regulation, which benefit enormously from the trypanosome genome projects and from the new genome-wide approaches recently introduced in trypanosome research. This volume covers the most important aspects of biosynthesis, processing, and functions of RNA in trypanosomes, ranging from transcription to RNA editing, mRNA splicing/translation/turnover, processing of transfer and ribosomal RNA, RNA interference, and current transcriptome-wide analyses. Recent progress in RNA-focused research in trypanosomatids promises to yield novel insights into trypanosome-specific features, as well as to reveal in the process new potential therapeutic strategies for combating these parasitic diseases.